Experimental damage tolerance evaluation of thick fabric carbon/epoxy laminates under low-velocity and high-velocity impact and compression-after-impact - Hoorn, N. van; Kassapoglou, C.; Turteltaub, S.R.; Brink, W.M. van den (Sage Journals, 2022)
Impact experiments of thick fabric carbon/epoxy laminate specimens, with small thickness ratio, are conducted at distinct energy levels and thicknesses to characterise the damage process. These specimens and loading conditions are representative of a new generation of critical structural components in aviation, such as wing spars, landing gear beams and fittings, that are increasingly being made entirely from composites. The tests address the need to better understand the damage process for specimens with a small thickness ratio since existing experimental impact data for large thickness ratio (thin laminates) may not be directly applicable. Two energy levels, two different fabric layups and two impact methods (drop-weight and gas-cannon) were used. Data from high-speed cameras were processed in a novel way, providing the force during impact. C-scans and micrographs were used to characterise damage. The results show that specimens with a thickness ratio of 5 (20 mm thick) experience more bending compared to specimens with a ratio 2.5 (40 mm thick). For gas-cannon impacts, this results in a higher delaminated area. The drop-weight impacts show almost no differences in damage size for the thickness range analysed. The influence of layup on the global impact response is negligible, but locally it can result in significant variations in dent depth. The dent depth scales linearly with the impact energy and the delaminated area linearly with the impact velocity. There is no clear correlation between the compression-after-impact failure mechanisms and the residual strength. Impact damage, at the current energy levels, showed a minimal reduction of residual strength.